Peter Singer, Rethinking Life and Death: The Collapse of our Traditional Ethics - Ivanova, Milena (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]